Some Forms of Synonymy in the Work of Hamza Humo - Enisa Gološ (Društvene i Humanističke Studije, 2017)
This paper focuses on synonymy, a paradigmatic relation that deals with individual words within acontext, and is based on the literary material of Hamza Humo. The first part of the paper presents the theoretical aspect of the analysis, which is constructed on eminent linguists' attitudes towards the mentioned problem. The second part of the paper is more focused on providing examples from the aforementioned corpus, which propose concretization and content richness of synonyms. The results have shown that synonymy as a lexical-semantic phenomenon has a special significance and may relate to the same term in the material world, such as kafana – krčma (pub – tavern), džamlija – odaja (glazed extension, e.g. wardrobe, cabinet – chambers) etc. The difference in the meaning of some lexemes depends on the individual perception, as well as the impact of emotion, social reality or some other semantic values that are essential in the process of decoding lexemes. At the same time, the distinctive examples of synonyms represent an exceptional contribution to lexicology based on the literary work of this Bosnian-Herzegovinian writer. In addition to specifying and referring to the specific features of these lexemes whose meaning is mainly confirmed in dictionaries, there are examples of lexemes, but in a small number, that are results of the writer's personal efforts.Special emphasis is put on the grouping of synonyms, such as vrat – šija (neck – back of the neck),zuriti – gledati (stare – look), kudrava – kovrdžasta (kosa) (curly (hair), kradom – krišom (gledati)(stealth – glance), the criteria of meaning and use in terms of lexeme substitutability within the samecontext, as well as proving the thesis of the existence/ non-existence of true synonyms and, overall, the notion of absolute synonymy. Moreover, the synonymous pairs in the paper are also sorted according to the type of words they belong to.Given that the analysis is based on lexical-semantic aspect, the chosen lexemes are observed within the context, because it is the context itself that gives the impression and makes each lexeme special. The analysis of characteristic lexemes, i.e. synonymous pairs, created a depiction of the extent of use of this lexical layer. In other words, this paper deals not only with the notion on how synonymy is utilized within Hamza Humo's literary works, but also on its frequency in the standard language and the language of everyday communication, as well as its importance in the communication as a whole.